Rituximab in steroid-dependent idiopathic nephrotic syndrome in childhood—follow—up after CD19 recovery - SELLIER-LECLERC, Anne-Laure; BAUDOUIN, Veronique; KWON, Theresa; MACHER, Marie-Alice; GUERIN, Valérie; LAPILLONNE, Hélène; DESCHENES, Georges; ULINSKI, Tim (Nephrology, dialysis, transplantation, 2012)
Rituximab (RTX) is a new treatment strategy in high-degree steroid-dependent idiopathic nephrotic syndrome (SDNS) in childhood. Thirty patients (nine girls) with SDNS with steroid side effects and previously treated with immunosuppressive drugs, mostly calcineurin inhibitors, were treated with RTX and included in this non-controlled single-centre study. Patient age at first RTX infusion was 12.9 ± 0.7 years. Our aim was to evaluate disease outcome after a minimum CD19 depletion period of 15 months obtained by repeated RTX infusion. Minimum follow-up after initial CD19 depletion was 24 months. During the RTX treatment period, seven patients had nephrotic syndrome relapses, six among them at the time of an intermittent CD19 recovery and one patient relapsed under CD19 depletion. The risk for these patients to relapse after the RTX treatment period was higher than in those without intermittent relapses. After definitive CD19 recovery over a follow-up of 17.4 ± 1.9 months, 19 patients (63%) did not relapse and 11 (37%) relapsed 4.3 ± 1 months after defininitive CD19 recovery. Among these 11 patients, 6 already had intermittent relapses during the RTX treatment period. Steroid and immunosuppressive treatment could be discontinued in all patients during CD19 depletion and was re-introduced in two after CD19 recovery. Fourteen patients had mostly benign and transitory side effects, which did not require RTX discontinuation. In conclusion, RTX treatment with a 15-month CD19 depletion period induced long-term remission after definitive CD 19 recovery in almost two-thirds the of patients without oral immunosuppressive drugs.